Low prevalence of combined linezolid- and vancomycin-resistant Enterococcus faecium from hospital admission screening in an endemic region in Germany - Heininger, Alexandra; Zimmermann, Stefan; Bootsveld, Carolin; Boutin, Sébastien; Nurjadi, Dennis (Journal of global antimicrobial resistance, 2020)
Background - The emergence and spread of linezolid and combined linezolid/vancomycin resistance in Enterococcus faecium (LVRE) is a major therapeutic challenge. Due to the unavailability of standardized selective culture media for LVRE screening, the detection of LVRE is laborious and costly. Systematic data on LVRE prevalence are scarce, and therefore, supportive evidence for the correct implementation of preemptive strategies is lacking. - Objective - We investigated the prevalence of LVRE in a vancomycin-resistant enterococci (VRE) endemic area in Germany in admission screening of high-risk patients for multidrug-resistant organisms to assess the necessity of LVRE screening. - Methods - We performed phenotypic testing for linezolid susceptibility in all patients (n = 2572) admitted to our hospital in the months of January, April, July and October 2018 with a positive VRE culture in their rectal admission screening swab. Eight isolates from seven patients with LVRE colonization were characterized by whole genome sequencing. - Results - Twenty-eight percent (712/2572) of screened patients were colonized by VRE. Seventy percent (497/712) of the isolates were available for testing and whole genome sequencing. A total of 1.4% (7/497) of VRE were LVRE, predominantly due to mutations of 23S rRNA. optrA, poxtA or cfr genes were not detected. Patients with LVRE colonization did not develop LVRE infections during their stay. - Conclusion - LVRE prevalence was low, and there was no evidence for the dissemination of linezolid resistance genes. Due to the low prevalence and the low risk of infection due to endogenous LVRE, we do not see the immediate necessity to introduce routine LVRE screening in our hospital.
Gesehen am 13.10.2020